Outcome of Cataract Surgery from Outreach Eye Camp - Suraj Senjan; Praveen Vashist; Sumit Malhotra (Delhi Journal of Ophthalmology)
Purpose: To share the concept of Reach in Programme (RIP) outreach eye care model and presents its outcome for the last five years of services (2009-13). Methodology: Reach in Programme: RIP is primarily Public-Private partnership model for outreach cataract intervention services with occasional involvement of Panchayati Raj Institution. Operable cataract patients were identified and referred to base hospital for intervention. Review of the RIP files and registers as primary sources of the data and cataract surgical records as secondary sources was done during June & July of 2013. Data were collected on those patients who had undergone surgery through outreach eye care services only. Data were entered in Microsoft excel and analyzed descriptively. The outcome was presented in terms of quantity and visual acuity status as a dichotomized optotype with a cut off of 6/60. Results: A total of 8735 (M=47.5%; F=52.5%) patients were operated in either eye during the five year period (2009-13) out of 9729 admitted. Of the total operated, 19% of them were less than 50 years of age. Very few were conventional surgery (2.2%); rests were phaco-emulsification technique. Preoperatively, 60% had visual acuity <6/60 in the operated eye. Six weeks' after surgery, 9.5% had poor visual outcome (<6/60) out of total follow up (415/5241) without any correction. Records of 61 patients were available for poor visual outcome that was attributed to surgical complications. Bullous keratopathy (27), posterior capsular opacity (16), uveitis (10) were maximally documented in decreasing numbers. Conclusions: Quite an amount of cataract surgery was conducted through our outreach eye care services with reasonably good quality. Strategy needs to be developed to improve follow up compliance as well as the reasons of poor outcome records.